The First Study Investigating the Clinical Outcomes of Boston Keratoprosthesis Type I Implantation in Indonesia - Johan A. Hutauruk; Kristian Goenawan; Suhardjo Suhardjo (Majalah Oftalmologi Indonesia, 2020)
Introduction and Objective: Boston keratoprosthesis (Boston KPro) is an artificial cornea (collar button design) for a severely damaged cornea that is not suitable for penetrating keratoplasty (PKP). One main advantage of Boston KPro type I is there is no need to perform tarsoraphy. There were no previous studies investigating the clinical outcome of Boston KPro implantation in Indonesia, therefore we aimed to investigate the visual outcomes, device retention, and complications following Boston KPro type 1 keratoprosthesis. Case Presentation: This study was a case series of 11 patients conducted at Jakarta Eye Center with 18 months follow up period. The inclusion criteria were patients with severe corneal diseases that are not amenable for PKP. We found that VA baseline were LP (±72.72%) and HM (27.27%) (mean VA baseline=2.51±0.14 logMAR or equal to HM – LP VA) which significantly improved to 1.09 ± 0.69 logMAR (equal to 6/60 Snellen, ±36.3% were near normal vision based on WHO criteria), p=0.007. Two cases (±16.7%) were still HM because of implant explantation with corneal melting. There were 80.5% retention rates at final follow-up and other complications were retroprosthetic membrane formation (26.7%), elevated IOP (13.9%), and sterile corneal stromal necrosis (17.8%).There was no endophtalmitis found in this study. Conclusion: Boston K-Pro type 1 is a recommended option for patients with multiple corneal graft failure. It provides promising visual outcome with good retention rates. The number of Boston K-Pro type 1 implantations should be increased to counterbalance the corneal blindness burden in Indonesia.